La irrevocabilidad de la adopción en el Ecuador: Análisis Jurídico desde la perspectiva de la patria potestad - Ruiz Quiranza, Lady Milena (2024)
Ecuadorian legislation establishes the irrevocability of adoption as a protective measure to guarantee a stable environment for the child or adolescent. However, parental authority acquired through adoption may be revoked for breach of duties. The analysis highlights norms that suspend parental authority, recognizing a legal vacuum and proposing revocability as a precautionary measure. Despite considering adoption as irrevocable in order to maintain a stable filiation, it is questioned whether the breach of parental authority duties is necessary for its revocation. It seeks to establish grounds for revocation in Ecuador, pointing out conflicts in protection due to the lack of strict compliance with rules oriented to the best interests of the child. This work highlights the importance of parental authority in the formation of a responsible filial bond suitable for the care of the child. It underlines the mutual need between adoption and parental authority in the institutional process. It is advocated for regulations that protect the rights of children and adolescents, including fair and timely revocation measures, in the face of possible consequences of omitting this process. Finally, a limitation in the consideration of preventive measures for the violation of rights is highlighted.